Trastorno de estrés postraumático y depresión en mujeres con signos de violencia doméstica en Lima Metropolitana, Perú - Agüero-Piazzini, Carmen del Rosario (2024)
The purpose of this article was to examine the association between posttraumatic stress disorder and depression in women presenting signs of domestic violence. It is an empirical study, with associative strategy and simple correlational predictive design. A total of 160 women aged 18-59 years (M = 31, SD = 6.60), selected by non-probability purposive sampling, participated. Three instruments were administered: the Woman Abuse Screening Tool (WAST) to screen for violence, as well as the Davidson Trauma Scale (DTS) and the Beck Depression Inventory (BDI-II) to associate both variables. The main results showed that 86% of the women with signs of domestic violence presented post-traumatic stress disorder symptoms, 98% severe indicators of depression and 2% moderate depression. Likewise, a statistically significant association (p<.05) with a medium effect size (Cramer's V = .34) was identified between the study variables. Finally, the Odss ratio (OR = 46.95) revealed that women with signs of domestic violence who present PTSD symptoms are 46.95 times more likely to suffer indicators of major depression, compared to those who do not present PTSD. Therefore, evidence shows that post-traumatic stress disorder and depression are significantly associated in the study population.